Mindful eating is associated with body mass index and might affect food preferences in adults in the early pandemic - Öztürk, Yasemin Ertaş; Kaya , Pınar Sökülmez (Acta Scientiarum. Health Sciences, 2024)
This study aimed to show alterations in body mass index (BMI) and food preferences and their associations with eating behaviors in the early pandemic. Four hundred and forty-three adults participated in this study. Data were collected using a web-based survey within a month after social distancing onset. Self-reported body weight and height were used to obtain the BMI trend. Alterations in eating habits (snacking, eating out, and main meal number) were collected. The mindful eating questionnaire, Mediterranean diet assessment tool, emotional eating scale, and depression inventory were applied. Multiple linear regression models were set to predict factors on BMI. Food preferences were shown according to mindful eating groups. BMI, snacking, and sleep duration increased in both sexes during social distancing. Nearly half of the participants reported weight gain, while one-fifth lost weight. Being overweight (from 36.0 to 38.7% for men, from 17.7 to 18.8% for women, and obese (from 10.7 to 12.7% for men and from 4.4 to 5.8% for women) increased. Eating out and regular sports activities decreased. The mindful eating scores, negative emotional eating, and positive emotional eating were the predictors of BMI after adjustment for age, sex, and regular sports activity. The only significant factor was mindful eating for the altered BMI. Consumption of bread, grains, seeds, sweet, salty, and fatty snacks, canned foods, pastry, milk puddings, bakery goods, jam and honey, sugar-sweetened fruit juices, and carbonated beverages increased in the low- more than the high-mindful eating group. In conclusion, BMI altered even in the early pandemic. Mindful eating was the only significant factor in the BMI increase. High carbohydrate and fat-contained food groups were more frequently preferred among the low-mindful eating group. Therefore, setting mindfulness practices might prevent eating disorder risks and promote public health.